Involvement of M1 Macrophage Polarization in Endosomal Toll-Like Receptors Activated Psoriatic Inflammation - Lu, Chih-Hao; Lai, Chao-Yang; Yeh, Da-Wei; Liu, Yi-Ling; Su, Yu-Wen; Hsu, Li-Chung; Chang, Chung-Hsing; Catherine Jin, S.-L.; Chuang, Tsung-Hsien (Mediators of Inflammation, 2018)
Psoriasis is a chronic inflammatory skin disorder that affects ~2%–3% of the worldwide population. Inappropriate and excessive activation of endosomal Toll-like receptors 7, 8, and 9 (TLRs 7–9) at the psoriatic site has been shown to play a pathogenic role in the onset of psoriasis. Macrophage is a major inflammatory cell type that can be differentiated into phenotypes M1 and M2. M1 macrophages produce proinflammatory cytokines, and M2 macrophages produce anti-inflammatory cytokines. The balance between these two types of macrophages determines the progression of various inflammatory diseases; however, whether macrophage polarization plays a role in psoriatic inflammation activated by endosomal TLRs has not been investigated. In this study, we investigated the function and mechanism of macrophages related to the pathogenic role of TLRs 7–9 in the progression of psoriasis. Analysis of clinical data in database revealed significantly increased expression of macrophage markers and inflammatory cytokines in psoriatic tissues over those in normal tissues. In animal studies, depletion of macrophages in mice ameliorated imiquimod, a TLR 7 agonist-induced psoriatic response. Imiquimod induced expression of genes and cytokines that are signature of M1 macrophage in the psoriatic lesions. In addition, treatment with this TLR 7 agonist shifted macrophages in the psoriatic lesions to a higher M1/M2 ratio. Both of the exogenous and endogenous TLR 7–9 ligands activated M1 macrophage polarization. M1 macrophages expressed higher levels of proinflammatory cytokines and TLRs 7–9 than M2 macrophages. These results suggest that by rendering macrophages into a more inflammatory status and capable of response to their ligands in the psoriatic sites, TLR 7–9 activation drives them to participate in endosomal TLR-activated psoriatic inflammation, resulting in an amplified inflammatory response. Our results also suggest that blocking M1 macrophage polarization could be a strategy which enables inhibition of psoriatic inflammation activated by these TLRs.